2010
DOI: 10.1103/physrevb.82.054504
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in molecule-intercalatedLixZrNClwith variable interlayer spacing

Abstract: Specific heat has been investigated in electron-doped Li x M y ZrNCl superconductors, in which interlayer spacing d can be controlled by the intercalation of organic molecules M. It has been revealed that, upon enlargement of d by molecule cointercalation, T c is enhanced concomitantly with the superconducting coupling strength whereas the density of states at the Fermi level is kept almost constant. Structural and spectroscopic analysis proved that the molecules are intercalated without affecting electronic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…With further increasing d, T c remains constant or decreases [39,40]. The specific heat measurements of Li x (Solv) y ZrNCl have revealed that the enhancement of T c is ascribed to concomitant enhancement of the pairing interaction [40]. Based on these results, it is concluded that the pairing interaction strongly depends on the Fermi surface warping along the k z direction, implying the relevance of charge and/or spin fluctuations rather than phonons.…”
Section: Phase Diagram and Effect Of Interlayer Distance On T Cmentioning
confidence: 90%
See 1 more Smart Citation
“…With further increasing d, T c remains constant or decreases [39,40]. The specific heat measurements of Li x (Solv) y ZrNCl have revealed that the enhancement of T c is ascribed to concomitant enhancement of the pairing interaction [40]. Based on these results, it is concluded that the pairing interaction strongly depends on the Fermi surface warping along the k z direction, implying the relevance of charge and/or spin fluctuations rather than phonons.…”
Section: Phase Diagram and Effect Of Interlayer Distance On T Cmentioning
confidence: 90%
“…The highest T c = 26.0 K is obtained in Ca 0.11 (THF) y HfNCl [33]. With further increasing d, T c remains constant or decreases [39,40]. The specific heat measurements of Li x (Solv) y ZrNCl have revealed that the enhancement of T c is ascribed to concomitant enhancement of the pairing interaction [40].…”
Section: Phase Diagram and Effect Of Interlayer Distance On T Cmentioning
confidence: 93%
“…Large organic molecules may also be included. [7][8][9] However, the origin of the high T c remains unknown, as the characteristics of this class of superconductors are unique. There is a low DOS at the Fermi level and a weak electron phonon cou- pling has been suggested both experimentally 10,11 and theoretically.…”
Section: Superconductivitymentioning
confidence: 99%
“…, are the monopole, dipole, and potential barrier, given in Eqs. (5), (9), and (11), respectively. The different parts of the Kohn-Sham potential are also shown in Fig.…”
Section: B Modelmentioning
confidence: 99%
“…In recent years, materials with reduced dimensionality have attracted a lot of attention because of their interesting physical properties and proposed applications range from electronics to sensing. In addition to graphene, which is probably the most studied two-dimensional (2D) material, monolayers or few-layer systems (nanolayers) of layered materials such as transition metal dichalcogenides [1][2][3][4][5][6][7] or chloronitrides [8][9][10][11][12] are gaining importance because of their intrinsic band gap. The possibility of doping these few layer systems with field-effect transistors (FETs) is particularly appealing.…”
Section: Introductionmentioning
confidence: 99%